MORTALITY EFFECT OF AZADIRACHTIN ON IN VITRO CULTURED CELLS OF RICE MOTH (CORCYRA CEPHALONICA ST.) LARVAE - Thanh Phượng, Lê Thị; Thắng, Nguyễn Tiến; Tuyến, Bùi Cách; Như Băng, Nguyễn Ngọc; Khoa, Phan Lê; Ngọc, Phan Kim (Vietnam Journal of Biotechnology, 2013)
The growing awareness of environmental hazards from synthetic pesticides and associated problems of pest resistance to pesticides, pests resurgence, detrimental effects on non-target organisms and environmental quality dictate the need for biopesticides, which are effective, economical and safe insecticides. Therefore, biopesticides originated from plants have been interested in recent years. One promising candidate for such potential pesticides is the neem tree (Azadirachta indica A. Juss). So far, over 120 kinds of bioactive compounds has been identified and the main representative of which is azadirachtin, a very complex limonoid mainly derived from neem seed kernel. Azadirachtin and other bioactive compounds of the neem tree have been reported to influence the insect’s activity and behavioural ecology as antifeedant, repellent, insecticidal, growth disrupting, ovipositional inhibiting, egg impairing agents and so on. However, there have been a few studies on affects of azadirachtin against insect cells. Specially, no study has ever recorded on  in vitro cultured cells of rice moth (Corcyra cephalonica), one of  common store-pests in many countries. This paper first describes the successful procedure of rice moth cell culture and affect of azadirachtin on them. Corcyra cephalonica cells derived from 3 - 5 day-old larvae were cultured in Grace medium supplemented with 10% FBS (fetal bovine serum). After the sufficient quantity of cultured cells collected, the cell suspension was diluted to the appropriate seeding concentration and transfered into the 96 well plates for  investigation on its growth curve. Mortality effect of azadirachtin on cultured cells of C. cephalonica was evaluated by trypan blue exclusion assay. The preliminary result showed that mortality rate of  C. cephalonica cells was 81.1% in the present of  5 µM azadirachtin on the fifth day after treament.